The Effectiveness of the KIP College Program in Supporting Student Studies - Nindi Lestari; Khalimatus Sa’diah; Agus Lestari (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to examine the effectiveness of the Smart Indonesia Card Program for College (KIP-Kuliah) in supporting the studies of students from underprivileged families. This study uses a descriptive method with a qualitative approach, through data collection techniques in the form of observation, interviews, and documentation. Based on the results of the literature review and interviews with KIP-Kuliah recipient students, it was found that this program significantly helps students in financing educational needs such as transportation, internet quota, and purchasing books, as well as increasing learning motivation. In addition, the KIP-Kuliah Program contributes to the development of student character, especially in building independence, leadership, and responsibility. However, this study also found several challenges, including delays in disbursement of funds and a tendency towards consumptive behavior among recipients of assistance. Problems in the information system and program monitoring also become obstacles in the evaluation and supervision of program implementation. Therefore, improvements to the fund disbursement system, recipient selection, character building, and strengthening of the integrated information system are needed to optimize the effectiveness of the KIP-Kuliah Program in the future. This study provides an overview that this program plays an important role in increasing equality of access to higher education in Indonesia, but still requires better management so that its benefits can be felt optimally by students.